Intra-Household Resource Dynamics and Food Security in Matatirtha VDC - Shrestha, Prativa (Economic Journal of Nepal, 2005)
This article ascertains the status of intra-household resource dynamics taking into consideration the access of females and males over these resources. Moreover, it analyzes the food security situation in Matatirtha Village Development Committee of Kathmandu District. It has been found from the qualitative data that the quality and quantity of food items was pretty poor implying that the frequency of food intake does not necessarily correlate with high quality food irrespective of the income level of the households.Economic Journal of Nepal Vol.28(4) 2005 pp.231-238